Microbial methane turnover at Marmara Sea cold seeps: a combined 16S rRNA and lipid biomarker investigation. Issue 1 (4th December 2012) - Chevalier, N.; Bouloubassi, I.; Birgel, D.; Taphanel, M.‐H.; López‐García, P.
Abstract Lipid biomarkers and their stable carbon isotopic composition, as well as 16S rRNA gene sequences, were investigated in sediment cores from active seepage zones in the Sea of Marmara (Turkey) located on the active North Anatolian Fault, to assess processes associated with methane turnover by indigenous microbial communities. Diagnostic 13C‐depleted archaeal lipids of anaerobic methane oxidizers were only found in one core from the South of Çinarcik Basin and consist mainly of archaeol, sn‐2 hydroxyarchaeol and various unsaturated pentamethylicosenes. Concurrently, abundant fatty acids (FAs) and a substantial amount of monoalkylglycerolethers (MAGEs), assigned to sulphate‐reducing bacteria, were detected with strong 13C‐depletions. Both microbial lipids and their δ13C values suggest that anaerobic oxidation of methane with sulphate reduction (AOM/SR) occurs, specially in the 10‐ to 12‐cm depth interval. Lipid biomarker results accompanied by 16S rRNA‐based microbial diversity analyses showed that ANME‐2 (ANME‐2a and ‐2c) archaea and Desulfosarcina/Desulfococcus and Desulfobulbus deltaproteobacterial clades are the major AOM assemblages, which indicate a shallow AOM community at high methane flux. Apart from the typical AOM lipid biomarker pattern, a 13C‐depleted diunsaturated hydrocarbon, identified as 7, 14‐tricosadiene, occurred in the inferred maximum AOM interval at 10–12 cm depth. Its isotopic fingerprint implies that its microbial precursor occurs in close association with the AOM communities. Interestingly, the presence of 7, 14‐tricosadiene coincides with the presence of the so‐far uncultured bacterial Candidate Division JS1, often detected in AOM areas. We propose the hypothesis that the JS1 bacterial group could be the potential source of 13C‐depleted tricosadiene. Future testing of this hypothesis is essential to fully determine the role of this bacterial group in AOM.